(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
This text addresses issues of restoration in Brazil today. To deal with this broad and complex theme, it is necessary to select some of the problems involved. In this article, the choice was to present some of the characteristics of preservation in Brazil to deepen a specific aspect: the tendency to disregard the theoretical contributions of restoration. In the last century, the vision about conservation in the country has shifted from a prevalent notion of heritage of exceptional value to the whole nation, to a more inclusive one, of heritage as bearer of reference to the identity and memory of the various groups that form the society. This process was accompanied by intense debates, with contributions coming from various fields of knowledge and different social groups, but the discussion on intervention criteria did not advance to the same extent. Therefore, the article will point out some of the characteristics of preservation in the country in order to discuss the tendency to discredit the theoretical principles of conservation and restoration, resulting in a prevalence of an exacerbated presentism. Key words: Cultural Heritage, Preservation, Theoretical Principles, Brazil.